Total Quality Management Development and Sharia Governance Efforts in Sharia Micro Financial Institutions to Improve Market Share - Ervicaninda Herry; Pramudia Yuli Eka Permana; Wisnu Bayu Aji; Ridan Muhtadi (LPPM NAROTAMA UNIVERSITY, Indonesia, 2019)
An important pillar in the development of Islamic microfinance institutions is Total Quality Management and Sharia Governance. This pillar is the main differentiator between conventional Islamic finance institutions. Institutional efforts to provide satisfaction to customers. The concept of quality (quality) for service and non-service basically includes various things that are focused on the customer. Shari'ah supervision is needed to ensure the implementation of Shari'ah principles in the financial institution, which is played by the Shari'ah Supervisory Board. Implicitly this shows that the practice of shari'ah microfinance institutions has not been concerned with shari'ah principles and the quality of good governance, one of the causes of reputation and public trust in Islamic microfinance institutions will also have an impact on community loyalty use the services of a Shari'ah microfinance institution. Improved reputation and customer trust can be used as an indicator of the success of the development of Islamic microfinance institutions and at the same time predicting their future success in order to increase market share.